ENGLISH EDUCATION DEPARTMENT ALUMNIâS PERSPECTIVE ON ENGLISH CURRICULUM DEVELOPMENT OF IAIN ANTASARI BANJARMASIN - Mufidah, Nida (Vidya Karya Jurnal Kependidikan, 2015)
Curriculum is the foundation of the teaching-learning process. One of the most important activities of the university is the development of curriculum or course outlines in consonance with the national and international demands and realities.This study was conducted to the 29 alumni of English Department of Faculty of Tarbiyah and Teachers Training. The data needed were the perspective, opinion and suggestion from the alumni of English Education Department Faculty of Tarbiyah and Teachers Training of IAIN Antasari Banjarmasin. These data gained from the result of questionaire, in depth-interview and documentation. This research found out Â that the course of English department curriculum has given perspective for alumni which most of them said that this curriculum has been run well and have good content. The courses have to be developed to address specific set of needs and to cover a given set of objectives. This English curriculumÂ  develop studentsâ awareness of the learning process and their role as learners by developing their knowledge and skills, how to use reference words,Â  design to assist them in independent study, awareness of their own learning styles, strengths and weakness, familiarity with various techniques, foreign culture andÂ  nature of learning strategies.